Clinical Characteristics of Functional Movement Disorders in the Stomatognathic System - Yoshida, Kazuya (Frontiers in Neurology, 2020)
Background: Functional (psychogenic) movement disorders often have distinguishable clinical features in the orofacial region. Tonic mandibular deviation accompanying ipsilateral downward and lateral lip pulling is the most common phenotype seen in patients with facial functional movement disorders. However, functional movement disorders in the stomatognathic system are underrecognized. Objective: This study aimed to evaluate clinical characteristics and phenomenology in patients with functional movement disorders in the stomatognathic system. Methods: 10-item inclusion criteria (point range: 0–10) for functional movement disorders in the stomatognathic system was produced based on previously established criteria for functional movement disorders and general signs of functional facial dystonia to determine subject inclusion. The criteria included inconsistency, incongruence, and paroxysm in symptoms; rapid onset; distractibility; suggestibility; static course; spreading to multiple sites; spontaneous remission; and lack of sensory tricks. Fifty-eight patients [42 women (72.4%), 16 men (27.6%); mean age: 47 years] scored over 7 points on the rating scale and were included in further analyses. Characteristic features including the pattern and site of abnormal movements were assessed in clinical examination. Results: Frequent items in the scale were inconsistent symptoms (93.1%), incongruous symptoms (91.4%), spreading to multiple sites (89.7%), paroxysmal symptoms (86.2%), and lack of sensory tricks (81%). Sixty percent of patients exhibited a pattern resembling dystonia. Some patients had a combination of organic and functional disease. Common involuntary movements included jaw deviation (74.1%), jaw closing (50%), lip pulling (34.5%), and tongue movement (31%). A functional dystonia phenotype (unilateral lower lip pulling and jaw deviation) was observed in 26 patients (44.8%). Characteristic features in functional stomatognathic movement disorders were rapidly repeating mandibular (lateral or tapping) and tongue movements (27.6%), which fluctuated in speed and direction. Conclusion: In 58 patients with functional movement disorders in the stomatognathic system, the functional dystonia phenotype was observed in 44.8%. Furthermore, 27.6% of patients showed the most characteristic type of functional stomatognathic movement disorders; very fast repeated jaw and/or lingual movements.